The Challenge of Islamic Education in 21st Century - Badrah Uyuni; Mohammad Adnan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractIslam is the way of life. And the Islamic education system is called a holistic approach to learning as it was in the early days of Islamic civilization. Islamic education, therefore, is considered and placed in a very noble position as it emphasizes the importance of the acquisition and dissemination of knowledge over other human activities. The background of this article sets out to assess the Challenges of Islamic Education in the 21st Century by bringing up some brief literature and analysis. In this article there are several topics related to the nature of Islamic education in Islamic education, the reality of Islamic education, Reform of Islamic education in the 21st century in the sectoral sector, curriculum, strengthening human resources, the Islamization of science by embodying Islamic values in science as part of education, the development and strengthening of Soft skills and management as well as entrepreneurial spirit is an inevitable need. But all of that will be able to work well and even become a force for the revival of the Islamic ummah if moral learning and gratitude for everything become the foundation for all reforms carried out in Islamic Education in the 21st Century and beyond.Keywords: Islamic Education, 21st Century, Challenge Abstrak Islam adalah cara hidup. Dan sistem pendidikan Islam disebut dengan pendekatan pembelajaran holistik seperti pada masa-masa awal peradaban Islam. Pendidikan Islam, oleh karena itu, dianggap dan ditempatkan pada posisi yang sangat mulia karena menekankan pentingnya perolehan dan penyebaran pengetahuan atas aktivitas manusia lainnya. Artikel ini dilatarbelakangi untuk mengkaji Tantangan Pendidikan Islam di Abad 21 dengan mengemukakan beberapa literatur dan analisis singkat. Pada artikel ini terdapat beberapa topik yang berkaitan dengan hakikat pendidikan Islam dalam pendidikan Islam, Realitas pendidikan Islam, Reformasi pendidikan Islam abad 21 pada sektor sektoral, kurikulum, penguatan sumber daya manusia, Islamisasi ilmu pengetahuan dengan mewujudkan Islam. nilai-nilai dalam ilmu pengetahuan sebagai bagian dari pendidikan, pengembangan dan penguatan Soft skill dan manajemen serta jiwa kewirausahaan merupakan kebutuhan yang tak terelakkan. Namun semua itu akan mampu berjalan dengan baik bahkan menjadi kekuatan bagi kebangkitan umat Islam jika pembelajaran akhlak dan rasa syukur atas segala hal menjadi landasan bagi semua reformasi yang dilakukan dalam Pendidikan Islam di abad 21 dan seterusnya.Kata Kunci: Pendidikan Islam, Abad 21, Tantangan